113 Effects of Sleep on Intrusive Symptoms and Emotion Reactivity in a Laboratory-Based Film Analogue Study. (3rd May 2021) - Nguyen, Anna Marie; Campbell, Rebecca; Vance, Abigail; Leen-Feldner, Ellen
Abstract: Introduction: Recent literature highlights the need to focus on the impact of intrusive symptoms as a possible risk factor for the development and maintenance of PTSD. Cognitive and sleep models also contribute to the further understanding of intrusive symptoms. Further emotion work emphasizes that disgust is an emotion closely associated with the emergence of posttraumatic stress symptomology following traumatic events. Methods: This study utilized a film eliciting disgust to examine the effects of acute sleep deprivation on the intensity of intrusive symptoms and emotion reactivity. Forty-nine college students were randomly assigned to sleep as usual or an acute sleep deprivation after watching a disturbing film. It was hypothesized that, relative to the control group, participants who were acutely sleep deprived would report higher frequency of intrusive symptoms and higher negative valence. Results: Findings were partially consistent with hypotheses. There were no group or interaction effects on intrusive symptoms, although participants across both groups reported significant decreases in negative valence and intrusive symptoms across the study (F(1, 47) = 10.30, p < 0.01). There was a significant interaction effect between sleep group and self-reported negative valence, where individuals in the sleep deprived group reported significantly higher valence than individuals in the control group, despite significant decreases in negative valence over time (F(1, 48) = 7.869, p < 0.01). Conclusion: Possible mechanisms that may contribute to the significant difference in valence may be due to higher order emotion regulation strategies that are compromised due to sleep loss. However, the significant decreases in negative valence and intrusive symptoms over time may be due to methodological factors or the type of sleep manipulation. Further work can address these challenges by using a larger sample size or examining the effects of chronic, partial sleep deprivation. Support (if any):